Fusion technology 1980. proceedings of the eleventh symposium, the Examination Schools, Oxford, UK, 15-19 September 1980. (Published for the Commission of the European Communities by Pergamon Press, 1981)
Fusion Technology 1980, Volume 2 contains the proceedings of the 11th Symposium on Fusion Technology held at the Examination Schools, Oxford, UK on September 15-19, 1980. As a continuation of the papers presented in the symposium, the book begins with a description of the data acquisition and control in fusion technology. Subsequent papers presented focus on power supplies, plasma engineering, and fusion materials. Various reactor studies reported in the symposium are also shown.